Risk of smoking cessation treatment dropout: a cohort to help (re)think care - Janaina Pereira da Silva; Adriana Ignácio de Pádua; Ruan Víctor dos Santos Silva; Felipe Lima dos Santos; Poliana Silva de Oliveira; Priscila Norié Araujo-Betetti; Joris Thievenaz; Cinira Magali Fortuna (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to evaluate the relative risk of smoking cessation treatment dropout during its intensive phase. Methods: a retrospective and quantitative cohort study was developed from the electronic medical records of individuals who started smoking cessation treatment between 2015 and 2019 at a specialty clinic in a city in the interior of São Paulo, Brazil. The relative risk of dropping out of treatment was calculated using the Poisson regression model. Results: it was observed that out of the 396 (100.0%) individuals who started the treatment, 109 (27.5%) abandoned it before the end of the intensive phase. For each one-year increase in age, the risk of dropping out of smoking cessation treatment decreased by an average of 2%. Conclusions: the risk of dropping out of smoking cessation treatment is higher among younger individuals. It is necessary to rethink the care offered to younger adults to promote the continuity of treatment.